Implikasi Landasan-Landasan Pendidikan - Rasid, Abdul (Pendidikan Agama Islam, 2018)
Educational foundations is as philosophical, sociological, and cultural foundations, which has important role for determining educational goals. Furthermore, scientifict and technological foundations will encourage the next for the future of education. Lexically, foundation means pedestal, foundation or base. Therefore, foundation is as the place for pedestaling or starting point or base on pedestaling. These are able to be materialistic. (eg: aeroplane foundation); it can also be conceptual (eg: educational foundation). Conceptual foundations are identical of assumption, as assumption can be divided into three kinds of assumptions, namely axioms, postulates and secret premises. Some implications of educational foundation are, religious implications that influencced by al-Ghazali thought especially in islamic education. The implication of educational philosophy is a set of philosophy that a serve as a strarting point in education. Social implications that’s occur in society, that case able to give an effect of education, both of science and activity. The scientific and technological implication are reconstructed by the development of science and technology in order to accelerate the realization of the nation’s integrity and superiority.